Case study of the socioenvironmental viability of tire collection by the Ecoponto Municipalities of the Middle Rio Piracicaba-MG for the cement industry demand (Research, Society and Development, 2019)
Environmental pollution, whether generated by solid waste or greenhouse gases, is continuously generated by current industrial production models. The cement industry generates significant amounts of CO2, and it is necessary to stimulate means so that the impacts generated are tolerable to the environment. The article aims to analyze the production process of the cement industry and its impacts on the environment and also to carry out a case study on the social and environmental feasibility of tire collection for the cement industry demand carried out by an Ecopoints that serves fourteen municipalities of the Minas Gerais state. The study was conducted through literature reviews, such as articles and dissertations and a visit with data collection from Ecoponto located in the city of João Monlevade-MG. The study analyzed the structure of the site and the average tire, with 266 tires collected during a semester, and 70% of the tires collected are destined for the cement industry for co-processing, which reduces waste and CO2 emissions. to the environment. Therefore, from the case study performed, it was evident that by the number of municipalities served, the average and the structure of the site is small compared to the total fleet of vehicles from the municipalities served by Ecoponto.